Meta-Analysis of Failure of Prehospital Endotracheal Intubation in Pediatric Patients. (2023)
Prehospital care is essential for airway preservation in pediatric patients who require early endotracheal intubation to improve oxygenation and prevent aspiration. However, high frequencies of failure of endotracheal intubation have been reported.